KEMAMPUAN REPRESENTASI MATEMATIS CALON GURU MATEMATIKA PADA MATA KULIAH TEORI PELUANG - Ruamba, Marthinus Yohanes; Mastur, Zaenuri; Kharisudin, Iqbal (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2022)
In understanding mathematics learning, representation is considered an entry point in solving various complex mathematical problems. The ability of mathematical representation is related to the expression of mathematical ideas using various ways, including written language, spoken language, pictures, symbols, examples, diagrams, graphs, or other real examples as representations. The research design used is mixed research (Mixed Method). The subjects in this study were 17 prospective mathematics teacher students, but then 3 (three) people were selected as subjects to be interviewed. Consists of subjects with high category (S1), subjects with medium category (S2), and subjects with low category (S3). Data collection was carried out using test instruments in the form of description questions in the probability theory course. From the test results, after being examined, students were selected to represent each category. Furthermore, by using the results of student tests, interviews were conducted to compare the results of interviews with student answers. The results of the written test and the results of the interview test were then analyzed to determine the student's representational ability. The results of this study indicate that students' mathematical representation skills in the probability theory course are still relatively low, this can be seen in 3 (three) subjects after matching the results of the written test and the results of the interview test. Individuals with high categories can meet the indicators of expression representation or mathematical equations and verbal representations. Subjects in the medium category were able to fulfill the indicators of mathematical representation or expression. Low subjects were not able to fulfill one of the three indicators of mathematical representation ability